Malignant Peripheral Nerve Sheath Tumour: CT and MRI Findings. (18th July 2013) - Sperandio, Massimiliano; Di Poce, Isabelle; Ricci, Aurora; Di Trapano, Roberta; Costanzo, Elisa; Di Cello, Pierfrancesco; Pelle, Fabio; Izzo, Luciano; Simonetti, Giovanni
Abstract : Malignant peripheral nerve sheath tumour (MPNST) is extremely rare malignancy in the general population, occurring more frequently in patients with Neurofibromatosis type 1 (NF1). In the literature five cases of MPNST arising from the parapharyngeal space (PPS) in patients without neurofibromatosis have been reported. We report imaging techniques in a patient with MPNST in the PPS, who had neither a family history nor sign of NF1. Computed tomography (CT) scan and magnetic resonance imaging (MRI) were performed for a correct therapeutic planning. CT and MRI findings were correlated with hystopathological diagnosis.